Let’s post more! The impact of foreign language social grooming on social media on learners’ enjoyment: a moderated mediation model - Wang, Fei; Wang, Xin (Frontiers in Psychology, 2025)
BackgroundDigital platforms play an increasing role in shaping family and community language practices, where everyday social grooming may shape the affective side of foreign language learning and maintenance. Yet it remains unclear how such social interaction on social media promotes learners’ foreign enjoyment, through which interpersonal communication processes, and for whom these benefits are realized given differing need for privacy.MethodsAn experiment with random assignment exposed 300 Chinese learners to high versus low intensity social grooming on Chinese social media platforms (e.g., WeChat, Weibo). After 1 week, participants completed validated measures of social capital, social support, enjoyment of language learning, and general need for privacy. A moderated sequential mediation analysis tested the proposed pathways and boundary conditions.ResultsHigher-intensity social grooming increased perceived social capital, which in turn fostered social support; both mechanisms independently and jointly elevated foreign language enjoyment of learners. A stronger need for privacy consistently weakened the direct and indirect effects of social grooming. Diagnostic checks supported the robustness of these patterns.ConclusionSocial grooming on mainstream platforms can enhance language enjoyment by activating social capital and support, but these benefits depend on learners’ privacy boundaries. By linking social interaction, boundary management, and affective experience, the study advances understanding of how digital practices shape language development and maintenance within the social and affective domain.